Застосування європейського досвіду проведення тендерів в Україні - Мацапура, О. В. (Ways to Improve Construction Efficiency, 2013)
The article deals with the application of the European experience of тенде-ditch inUkraine. The author of the unified approaches of various scholars and practitioners in the concept of «the tender» and formulated its own concept of «tender». And also identified the main tasks of the tender.